2023
DOI: 10.1177/03611981231165019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of Freeway Weaving Section Length on Level of Service Based on Microsimulation

Abstract: At freeway weaving sections, traffic congestion and accidents are frequent because of the disturbance generated by merging or diverging vehicles. To reduce the disturbance and accordingly improve the level of service (LOS), an appropriate length of weaving section should be established. According to the US-HCM, the weaving section density, which is a surrogate for LOS, is determined by weaving length, traffic volume, and weaving volume ratio. However, it is not yet clear whether the US-HCM accurately estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Research on traffic management for vehicles has shown that genetic algorithms are highly effective for calibrating and validating networks [13,14], and genetic algorithms have been shown to be particularly effective for analyzing traffic characteristics, in terms of safety, operational efficiency, and environmental performance [15,16].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on traffic management for vehicles has shown that genetic algorithms are highly effective for calibrating and validating networks [13,14], and genetic algorithms have been shown to be particularly effective for analyzing traffic characteristics, in terms of safety, operational efficiency, and environmental performance [15,16].…”
Section: Related Workmentioning
confidence: 99%
“…The third step is to examine the convergence conditions of the impact measures and select the combination of input variables that gives the best impact measure values. The convergence conditions of the impact measures are 0.05 or less for MAPE and RMSPE and 5 or less for the GEH used in traffic analysis models, and if the conditions converge, the level of simulation is considered reasonable [16]. If the convergence condition is not met, a new combination is generated and returned to the second step until the convergence condition is met.…”
Section: Optimizing Vissim Input Variables With Genetic Algorithmsmentioning
confidence: 99%